Measuring Corruption in Eastern Europe and Central Asia : A Critique of the Cross-Country Indicators - Knack, Stephen (World Bank, Washington, DC, 2012)
This paper assesses corruption levels and trends among countries in the transition countries of Eastern Europe and Central Asia (ECA) based on data from several sources that are both widely used and cover most or all countries in the region. Data from firm surveys tend to show improvement in most types of administrative corruption, but little change in "state capture" in the region. Broader, subjective corruption indicators tend to show somewhat greater improvement in ECA than in non-ECA countries on average. A "primer on corruption indicators" discusses definitional and methodological differences among data sources that may account in large part for the apparently conflicting messages they often provide. This discussion concludes that depending on one's purpose, it may be more appropriate to use data from a single source rather than a composite index because of the loss of conceptual precision in aggregation. A second conclusion is that the gains in statistical precision from aggregating sources of corruption data likely are far more modest than often claimed because of interdependence among data sources. The range of detailed corruption measures available in firm surveys are exploited to show that broad, perceptions-based corruption assessments appear to measure primarily administrative corruption, despite their stated criteria placing great weight on "state capture." Finally, the paper emphasizes the need for scaling up data initiatives to fill significant gaps between our conceptual definitions of corruption and the operational definition embodied in the existing measures.